2019
DOI: 10.1080/15548627.2019.1659654
|View full text |Cite
|
Sign up to set email alerts
|

PAQR3 suppresses the growth of non-small cell lung cancer cells via modulation of EGFR-mediated autophagy

Abstract: Macroautophagy/autophagy is an evolutionarily conserved intracellular process that recycles and degrades intracellular components to sustain homeostasis in response to deficiency of nutrients or growth factors. PAQR3 is a newly discovered tumor suppressor that also regulates autophagy induced by nutrient starvation via AMPK and MTORC1 signaling pathways. In this study, we investigated whether PAQR3 modulates EGFRmediated autophagy and whether such regulation is associated with the tumor suppressive activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 39 publications
(61 reference statements)
2
33
0
1
Order By: Relevance
“…Recently, autophagy has emerged as a promising target for cancer treatment, and induction of autophagyassociated cytotoxic death through blockade of autophagic flux has been increasingly recognized as a novel cancer therapeutic strategy [19][20][21]. In the present study, we indicated that ARCSP has an effective antitumor effect on cervical cancer cells.…”
Section: Discussionmentioning
confidence: 50%
“…Recently, autophagy has emerged as a promising target for cancer treatment, and induction of autophagyassociated cytotoxic death through blockade of autophagic flux has been increasingly recognized as a novel cancer therapeutic strategy [19][20][21]. In the present study, we indicated that ARCSP has an effective antitumor effect on cervical cancer cells.…”
Section: Discussionmentioning
confidence: 50%
“…Cell proliferation assay CCK-8 is a widely used method for detecting cell proliferation [19]. Ten hours after the cell damage, 10 μl Cell Counting Kit-8 (CCK-8) (Biosharp Life Sciences, Hefei, China) reagent was added to each well, and the optical density was measured at 450 nm.…”
Section: E920855-2mentioning
confidence: 99%
“…Growing evidence indicates a close correlation between autophagy and lung cancer. PAQR3 was demonstrated to suppress the tumor progression of NSCLC cells by modulating EGFR-regulated autophagy [25]. The downregulation of autophagy facilitated the anti-LUAD efficacy of Shh pathway suppression, thus highlighting a potential approach for LUAD therapy [26].…”
Section: Discussionmentioning
confidence: 98%